Child Psychology: A Basic Understanding of Child’s Behavior: Understanding and Nurturing a Child's Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Childhood is a beautiful and carefree phase of life and also the best learning time. Child psychology is a very delicate matter. These early days of one’s lifetime define their future. This paper discusses how abnormal behavior of a child is to be identified and shares some useful parenting tips. Child needs to be appreciated and valued. Sense of responsibility should be dwelled in early stages.